A urban and social dynamic in an informal district: Case of Oued Skhoune - Guelma - Algeria - Saidi, Tahar; Hamadi, Nada (Journal of Architecture and environment of child, 2023)
Urbanization accelerated as globalization spread industry and technology to the far ends of the earth. The latter is urbanizing and the rate of urbanization over time provides information on the speed of propagation of the phenomenon. This urbanization was massive and rapid propelling the urban fact at the heart of these changes. Algerian cities are undergoing a transition from which new configurations are beginning to appear under the joint action of formal and informal urbanization. A prospect of renewal is looming on the horizon and the medium-sized town of Guelma is a good example. This city in eastern Algeria of Roman birth: ancient Calama underwent colonial urbanization until independence. Next to the colonial city was born a slum of Oued Skhoune, which has seen a radical transformation over the years. This phenomenon may be unique; a slum at the gates of the city of Guelma integrates with the urban and becomes a dominant urban fact in the city by its centrality, which is a paradox. In this city, we are witnessing a territorial and social dynamic where a structure with a border experiences an institutional dynamic through a process of integration.